Knowledge, beliefs, and practices related to cancer screening and prevention in Lebanon: community and social media users' perspectives. Issue 4 (17th September 2020) - Telvizian, Talar; Al Ghadban, Yasmina; Alawa, Jude; Mukherji, Deborah; Zgheib, Nathalie K.; Sawaf, Bisher; Nasr, Rihab; Bardus, Marco
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Common to many countries in the Middle East, Lebanon has an increasing cancer burden; however, national screening programs are limited to breast cancer. The literature on cancer screening practices and beliefs is scarce. This cross-sectional study investigates the knowledge, beliefs, and practices related to the prevention and screening for breast, cervical, colon, lung, and skin cancers among Lebanese residents, recruited through social media advertisements and community outreach activities. Methods: Participants filled an anonymous questionnaire either via a web-based interface or using tablets distributed at primary health clinics. The characteristics of the two cohorts were compared with chi-square and t -tests. We performed descriptive analysis, followed by multivariate logistic regression for predictors of cancer screening. Results: A total of 407 participants completed the survey online, and 262 filled the study in tablets available at primary care clinics. The two samples were significantly different in terms of age, education, and perceived socioeconomic status. Online participants demonstrated higher knowledge and higher participation in screening practices than their counterparts recruited through community outreach. Mammography (44.7% online and 39.9% in-person), and cervical cancer screening (44.5% online and 36.7% community) had the highest participation rates. In both samples, participants who were older and more educated were more likely to report engagement with cancer screening practices. Conclusions: Our study revealed significant knowledge gaps in cancer prevention and screening. Different sampling techniques accessed diverse populations, highlighting the need for educational messages and targeted screening programs to be inclusive of socio-economically disadvantaged communities with low education and health literacy.